CFD Analysis of Electric Vehicles Battery Pack: A Research Study - Rushikesh Tayade; Vinay Verma; Sumit Bamane; Abhishek Talekar; Vishnudas A.V.L. Chodankar (International Journal of Electrical Power and Machine Systems, 2024)
The goal of the project is to keep the battery temperature within the specified range and to improve the battery pack's performance under different temperature settings. To achieve these goals, we employ software to analyze the data and provide the necessary output. With model-based design, you can understand the dynamic behavior. For this project, a CAD model was produced with Creo Parametric. We used the STAR CCM+ Software for analysis and meshing on that. To absorb the heat from the battery cells, we placed a Silica Pad between the cooling plate and the battery pack. We have a 32-cell battery pack. Several computer simulations and mathematical modeling are used to analyze the cooling plate. We found that by varying the flow rate, there was a 10ᵒ C temperature change. 53°C was the temperature attained for this project. To do so, the flow rate is maintained at 0.9 m/s. To assess pack performance, a 3D CFD simulation can examine flow routes in addition to pressure drop, velocity, heat transfer, and local temperature. We consider the flow rate and silica absorption rate after assuming the heat dissipation rate of the cells. In our findings, the primary goal of the cooling channel study varies depending on the design in order to minimize temperature differential and pressure loss. We investigated the temperature differential between water and ethylene glycol mixture.
Keywords: EV; battery pack; cooling channel; copper tubes; lithium-ion phosphate battery; silica pad